Cardiac transthyretin wild-type amyloidosis (ATTRwt): a prospective study of 400 patients followed at the Italian referral center. (25th November 2020) - Milani, P; Obici, L; Mussinelli, R; Basset, M; Manfrinato, G; Nuvolone, M; De Matteis, G; Sabena, A; Benigna, F; Cavenaghi, G; Foli, A; Perlini, S; et al.
Abstract: Background: Cardiac wild type transthyretin (ATTRwt) amyloidosis, formerly known as senile systemic amyloidosis, is an increasingly recognized, progressive, and fatal cardiomyopathy. Two biomarkers staging systems were proposed based on NT-proBNP (in both cases) and troponin or estimated glomerular filtration rate, that are able to predict survival in this population. The availability of novel effective treatments requires large studies to describe the natural history of the disease in different populations. Objective: To describe the natural history of the disease in a large, prospective, national series. Methods: Starting in 2007, we protocolized data collection in all the patients diagnosed at our center (n=400 up to 7/2019). Results: The referrals to our center increased over time: 5 cases (1%) between 2007–2009, 33 (9%) in 2010–2012, 90 (22%) in 2013–2015 and 272 (68%) in 2016–2019. Median age was 76 years [interquartile range (IQR): 71–80 years] and 372 patients (93%) were males. One hundred and seventy-three (43%) had atrial fibrillation, 63 (15%) had a history of ischemic cardiomyopathy and 64 (15%) underwent pacemaker or ICD implantation. NYHA class was I in 58 subjects (16%), II in 225 (63%) and III in 74 (21%). Median NT-proBNP was 3064 ng/L (IQR: 1817–5579 ng/L), troponin I 0.096 ng/mL (IQR: 0.063–0.158 ng/mL), eGFR 62 mL/min (IQR: 50–78 mL/min). Median IVS was 17 mm (IQR: 15–19 mm), PW 16 mm (IQR: 14–18 mm) and EF 53% (IQR: 45–57%). One-hundred and forty-eight subjects (37%) had a concomitant monoclonal component in serum and/or urine and/or an abnormal free light chain ratio. In these patients, the diagnosis was confirmed by immunoelectron microscopy or mass spectrometry. In 252 (63%) the diagnosis was based on bone scintigraphy. DNA analysis for amyloidogenic mutations in transthyretin and apolipoprotein A-I genes was negative in all subjects. The median survival of the whole cohort was 59 months. The Mayo Clinic staging based on NT-proBNP (cutoff: 3000 ng/L) and troponin I (cutoff: 0.1 ng/mL) discriminated 3 different groups [stage I: 131 (35%), stage II: 123 (32%) and stage III: 127 (33%)] with different survival between stage I and II (median 86 vs. 81 months, P=0.04) and between stage II and III (median 81 vs. 62 months, P<0.001). The UK staging system (NT-proBNP 3000 ng/L and eGFR 45 mL/min), discriminated three groups [stage I: 170 (45%), stage II: 165 (43%) and stage III: 45 (12%)] with a significant difference in survival: between stage I and stage II (86 vs. 52 months, P<0.001) and between stage II and stage III (median survival 52 vs. 33 months, P=0.045). Conclusions: This is one of the largest series of patients with cardiac ATTRwt reported so far. Referrals and diagnoses increased exponentially in recent years, One-third of patients has a concomitant monoclonal gammopathy and needed tissue typing. Both the current staging systems offered good discrimination of staging and were validated in our independent cohort. Funding Acknowledgement: Type of funding source: None